Analysis of Student Interaction and Social Skills in Game Activities in Elementary School in Indonesian Context - Zuni Eka Tiyas Rifayanti; Evi Rizqi Salamah; Poonkeat Monkonsawasd; Shelly Andari (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Social skills are one of the basic skills that students must have. How important social skills students must have. Elementary school students are expected to be able to recognize and implement social skills in their future lives. However, in practice at school, students have fewer social skills. Due to the lack of interaction and joint learning activities between students in elementary schools. Through learning activities at school, communicating, and even playing. This research aims to analyze the types of games that can foster interaction and social skills in elementary school students. Method: This research uses a qualitative research method with a descriptive approach. The research subjects were 15 elementary school students in Wringinrejo, Mojokerto. Research stages (1) in the preparation stage, the researcher pr, prepares a research plan and creates interviews, observations, documentation, and guidelines. (2) Implementation Stage, the researcher conducted a field study by carrying out observation and interviews, as well as taking documentation; 3) Findings Results: The researcher analyzed the findings and made conclusions from the research results and continued with the final stage, namely (4) Research Reporting Stage using observation data, interviews, and documented. Result: The results of this research show that the social skills of elementary school students are excellent through group play activities such as mazes and marbles are suitable for solitary and social play because they are proven to stimulate children to interact socially in the physical process and improve their social skills.Novelty: The researcher's hope for future researchers is to look more deeply at students' social skills at the elementary school level to have more innovative strategies, media, or other methods in instilling students' social skills.